(untitled) (International Educators Conference, 2025)
The article examines how the concept of macroproposition contributes to the comprehension of literary texts. It emphasizes that identifying macropropositions allows for uncovering deeper semantic layers, establishing thematic and ideological coherence, and activating the reader’s cognitive involvement. This perspective offers a valuable methodological framework for the analysis and interpretation of literary works.